프로축구 관람자의 소비감정, 관람만족이 재관람 의도에 미치는 영향 - 김기탁; Ki Tak Kim; 강준호; Joon Ho Kang (Ch'eyuk kwahak yŏn'gu, 2006)
인간은 감정적 동물이다. 따라서 감정적 요소를 배제하고 인간행동의 의사결정과정을 설명하는 것은 한계가 있다. 이에 심리학, 소비자학, 마케팅 분야 등에서는 소비자의 행동을 이해하는데 감정의 역할을 중요시 해 왔다. 그러나 스포츠 상황, 특히 관람스포츠 상황에서는 감정의 역할을 규명한 연구가 극히 미미한 실정이다. 이에 본 연구는 관람스포츠에서 감정의 역할을 규명하고 마케팅 이념의 중심인 만족과의 관계를 분석하여 관람자의 행동의도를 설명하려는 목적으로 수행하였다. 본 연구의 대상은 부천과 서울 두 곳의 프로축구 경기 관람자를 대상으로 이루어졌으며, 총 310부의 설문지를 배포하고 293부를 회수하여 270부를 실제 분석에 이용하였다. 자료처리는 SPSSWIN Ver. 12.0과 AMOS 4.0을 이용하여 빈도 분석(frequency analysis), 기술통계분석, 상관분석, 신뢰도분석, 확인적 요인분석(confirmatory factor analysis), 구조방정식모형(Structural Equation Model)등을 실시하였다. 연구결과, 관람객의 긍정적 감정은 관람만족에 정(+)적인 영향을 미치고, 부정적 감정은 부(+)적인 영향을 미치며 영향력의 크기는 긍정적 감정이 큰 것으로 나타났다. 또한 긍정적 감정과 부정적 감정 모두 재관람 의도에는 직접적인 영향을 미치지 않는 것으로 나타났으며, 관람만족은 재관람 의도에 유의한 영향을 미치는 것으로 나타났다. 이러한 결과는 다른 서비스 상품에서와 마찬가지로 관람스포츠에서도 소비감정의 중요성이 확인되었다고 결론지을 수 있다. The role of consumption emotion is an important subject of study in consumer behavior. We can expect easily the role of consumption emotion is very important in sport consumption because sport related services are said to be consumed primarily for hedonic purposes; however, studies related to consumption emotion are insufficient in this field, especially spectator sport consumption. This study was to analyze structural relationships among consumption emotion, consumer satisfaction, and re-attend intention of professional sport spectators. Data were collected from two games of K-league. Using quota sampling and convenience sampling method, a total of 293 samples responded to the instrument containing consumption emotion, spectators` satisfaction, re-attend intention and demographic variables. After screening data, 270 samples were used for this study. The statistical techniques for data analysis were frequence analysis, descriptive analysis, reliability analysis, correlation analysis, confirmatory factor analysis, and structural equation modeling by SPSS 12.0 and Amos 4.0 programs. The result showed that positive consumption emotion appeared to have a positive effect on spectators` satisfaction and negative consumption emotion had a negative effect on spectators` satisfaction. And, the effect of spectators` satisfaction on re-attend intention was positive. The effect of positive consumption emotion on re-attend intention was positive and the effect of negative consumption emotion in re-attend intention was negative as hypothesized, but not statistically significant.